Development Learning to Recognize Hijaiyah Letters in Reading and Writing the Qur'an Based on Application Canva to Improve Learning Motivation - Iqbal, Muhammad; Asrori, Asrori; Hadi, Muhammad Fazlurrahman (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The phenomenon in Indonesia lately shows that the level of reading the Qur'an has decreased, the same thing is experienced in Putera Harapan Kindergarten where the problem faced is the low level of ability to read the Qur'an among children, which is caused by learning methods that are less interesting and considered monotonous by children. So that children lack enthusiasm for learning the Koran. Therefore, this study aims to develop learning the introduction of hijaiyah letters in reading and writing the Qur'an based on the Canva application at Putera Harapan Kindergarten, with a focus on increasing children's learning motivation. The method used is Research and Development (R&D) with experimental techniques, which includes stages, the development process begins with identifying problems and analyzing needs, designing learning media using the Canva application, design validation, product trials on groups of children and revision. The results showed that the use of Canva application-based learning media can significantly increase children's learning motivation, seen from the increase in learning motivation before and after using the media. Thus, the Canva app proves to be effective in overcoming the problem of monotonous and uninteresting learning, as well as being able to create a more interactive and fun learning atmosphere for children.